2021
DOI: 10.1021/acs.orglett.0c04155
|View full text |Cite
|
Sign up to set email alerts
|

Rh(III)-Catalyzed C–H Olefination Cascades to Divergently Construct Diverse Polyheterocycles by Tuning Manipulations of Directing Groups

Abstract: Inspired by the diversity created by nature, organic chemists have been using a divergent strategy to improve the synthetic efficiency of diverse molecules. Transition-metal-catalyzed C–H functionalization has become one of the most straightforward, powerful, and atom-economical methods to construct complex scaffolds. However, C–H activation initiated divergent transformation to prepare diverse molecules is still limited. To address this challenge, we herein developed Rh­(III)-catalyzed C–H olefination/annulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Our previous study has identified that 2‐phenylquinazolin 4‐(3 H )‐one, which is similar to 3‐aryl‐2 H ‐benzo[1,2,4]thiadiazine 1,1‐dioxide, undergoes two different annulation with diphenylacetylene. [ 36 ] And the selective annulation of benzothiadiazine‐1,1‐dioxide with aryl aldehydes has also been observed before. [ 15 ] To determine whether the annulation occurred at N2 or N4 position in this reaction, The structure of compound 3ma was established by a single crystal X‐ray analysis, and annulation at N4 position was observed.…”
Section: Resultsmentioning
confidence: 75%
“…Our previous study has identified that 2‐phenylquinazolin 4‐(3 H )‐one, which is similar to 3‐aryl‐2 H ‐benzo[1,2,4]thiadiazine 1,1‐dioxide, undergoes two different annulation with diphenylacetylene. [ 36 ] And the selective annulation of benzothiadiazine‐1,1‐dioxide with aryl aldehydes has also been observed before. [ 15 ] To determine whether the annulation occurred at N2 or N4 position in this reaction, The structure of compound 3ma was established by a single crystal X‐ray analysis, and annulation at N4 position was observed.…”
Section: Resultsmentioning
confidence: 75%
“…Recently, we have disclosed a C–H activation/annulation cascade reaction with iodonium ylides . Given that our group are committed to develop efficient synthetic routes of C–H activation and carbenoid insertion reactions, we anticipated that 3-phenyl-pyridotriazole could react with diazodicarbonyl compounds via transition metal-catalyzed C–H activation followed by sequent denitrogenation and insertion into the O–H bond to construct fused isochromene scaffolds. If successful, this cascade intramolecular annulation combining C–H activation and carbene insertion would provide oxygen-containing heterocycles in an efficient one-pot manner and expand the utility and transformations of pyridotriazoles.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key synthetic methodologies is the C-H bond activation process that enables a straightforward access to several important and innovative compounds [14][15][16][17][18]. In the last few years, metals such as ruthenium [19][20][21], rhodium [22][23][24], palladium [25][26][27], and iridium [28][29][30] have been widely applied as catalysts for this matter, including in the synthesis of bioactive substances. Although catalysts based on these metals, are known to be efficient in C-H bond activation reactions affording the products in good yields and mild conditions, they are also known to be usually expensive.…”
Section: Introductionmentioning
confidence: 99%